Linear representation of pitch height in the SMARC effect - Prpic, Valter (Array, 2018)
The Spatial-Musical Association of Response Codes (SMARC) effect consists in faster and more accurate responses to low (vs. high) pitched tones when they are executed in the bottom/left (vs. top/right) space. This phenomenon has many similarities with the Spatial-Numerical Association of Response Codes (SNARC) effect which, however, has been more extensively investigated and theoretically debated. The first theoretical account of the SNARC effect suggests the existence of a direct mapping between the position of a number on a mental number line and the external space of response execution. Conversely, following accounts claim that numbers are automatically categorized in two opposing categories (e.g., small vs. large) and then associated to response alternatives (left vs. right). A modified task, consisting in unimanual close/far responses relative to a reference key, has been employed to disentangle between the opposite theoretical accounts of the SNARC effect. However, this modified task has never been applied to pitch height and currently there are no specific theoretical accounts for the SMARC effect. The aim of this study is to fill this gap of knowledge. Contrary to what has been found for numbers, our data are more in line with the "direct mapping" account and suggests a linear representation of pitch height. Our data suggest that SNARC and SMARC effects might have different origins and might require different theoretical accounts.